Teacher Performance and The Role of Organizational Culture - Abdul Chalim; Trimey Liria Hutauruk; Najwa Syarofa; Sri Hudiarini; Fadloli Fadloli (International Journal of Education and Literature, 2023)
In the field of education, organizational culture and the school environment are critical variables that must be considered. Of course, this immediately improves teacher performance, which in turn improves school quality. In practice, State Elementary Schools in the Buah Batu District have established an organizational culture and created a welcoming school atmosphere, yet this appears to be insufficient. It is still discovered that instructors' behavior in carrying out their tasks does not adhere to the established culture, and there are many teachers who have not earned teaching credentials, which is an intriguing issue to explore. The quantitative approach used in this study is descriptive statistical analysis. 78 respondents were given questionnaires with the expectation that they would be able to answer the research objectives. SPSS version 25 was used for statistical testing. According to the findings of the research, organizational culture and the work environment have an impact on teacher performance, both individually and collectively. Several recommendations are made to school principals, supervisors, and instructors in the study that will help them enhance their performance.